About III International school of young ethnosociologists in Mongolia and presentations about the project of Tuvan youth - Kan, Valeriya S. (The New Research of Tuva, 2010)
The article is considered some results of professional business trip in Mongolia (with RHF 090163205 a/T grant supporting) including the member’s impressions of the Third International school of young ethnosociologists.